Euro Area Policies : 2016 Aticle IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Euro Area. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the recovery in euro area has strengthened recently. Lower oil prices, a broadly neutral fiscal stance, and accommodative monetary policy are supporting domestic demand. However, inflation and inflation expectations remain very low, below the European Central Bank's medium-term price stability objective. Euro area GDP growth is expected to decelerate from 1.6 percent in 2016 to 1.4 percent in 2017, mainly owing to the negative impact of the U.K. referendum outcome. Growth five years ahead is expected to be about 1.5 percent, with headline inflation reaching only 1.7 percent.